Relationship of Spirituality with Morbidity and Mortality in Patients with Coronary Artery Disease undergoing CABG Surgery at Shariati Hospital - Jamshid Bagheri; Nasim Shayan; Mohammad Mahdi Bagheri; Matineh Heidari (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Coronary artery disease is the leading cause of death in most countries. Although the relationship between spirituality and health has been confirmed in various studies, the relation in this specific case has not been investigated. Therefore, the present study was conducted to investigate the relationship of spirituality with morbidity and mortality in patients with coronary artery disease who underwent CABG surgery. Method: This cross-sectional study was performed on patients with coronary artery disease who had undergone CABG at Dr. Shariati Hospital in Tehran over the time period from December 2012 to December 2013. The data collection tools were a data gathering checklist based on patients' records and respective physician's confirmation and the Spirituality questionnaire (Hall and Edwards, 1996). Data were analyzed using Mann-Whitney, Kruskal-Wallis, and Spearman correlation coefficient. All ethical issues were observed in this study and the authors of the article have not reported any conflicts of interest. Results: The findings of the relationship between the six subscales of spirituality with morbidity and mortality showed that with an increase in the median score of disappointment subscale, the incidence of infection, tamponade, PVC and AF increased and by increasing the median score of awareness subscale, the incidence rate decreased (P<0.05). There was a significant positive correlation between the hospital stay and disappointment subscale (P=0.003, r=0.291). Mortality also decreased in patients who were more knowledgeable (p<0.05). Conclusion: The results of the research indicate that spirituality correlates with the incidence of morbidity and mortality after CABG surgery. Therefore, effective solutions such as considering the spiritual issues in the patients' treatment process and training appropriate psychological techniques should be used to expedite their recovery. For downloading the full-text of this article please click here.